"Jy is net 'n sandkorrel, maar só is alle mense" - Nadenke oor Psalm 131 - Viviers, Hennie (Verbum et ecclesia, 1998)
"You are only a grain of sand, but so are all people" - Reflections on Psalm 131: W S Prinsloo has convincingly proved that humbleness and surety is what Psalm 131 is all about. His "text-immanent" approach allowed him to have an excellent grasp of this text and all texts that he studies. Utilising a newcomer on the methodological scene, namely Robbins' socio-rhetorical analysis, it is remarkable how Prinsloo's insights into PsaLm 131 could be used as basis for the "widening of interpretive horizons" on this psalm.